Effectiveness of dry needling in the treatment of neck pain and disability associated with myofascial trigger points - ŞANAL TOPRAK, CANAN (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: The aim of this study is to evaluate the effectiveness of dry needling (DN) with fast-in and fast-out technique for myofascial trigger points (MTrPs) in the upper trapezius muscle associated with neck pain. Patients and Methods: Patients aged 18-70 years, who have had neck pain at least one active MTrP in the upper trapezius muscle treated with DN, were included in the study. Pain and disability were assessed with Numeric Rating Scale (NRS) and Neck Disability Index (NDI) before treatment (T0), after first session (T1) and after last session (T2). Number of MTrPs where DN was performed and the number of DN sessions were recorded. Patients were evaluated based on the minimal clinically important change (MCIC) scores for NRS and NDI. Results: A total of 76 patients (Female: 67, Male: 9) were included in the study. Median number of DN sessions was 3 and median of MTrPs that DN performed was 4. Both NRS and NM showed significant improvement at T1 and T2. More than 90% of patients had MCIC at T1 and T2. Conclusion: Dry needling with fast-in and fast-out technique is effective for pain and disability management in patients with neck pain due to MTrPs.
Keywords: Dry needling; Myofascial trigger points; Neck pain; Neck disability; UPPER TRAPEZIUS; INDEX; RELIABILITY; VALIDITY; REMOTE; SCALE